2014
DOI: 10.1002/2014jc010244
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of surface signatures of Mediterranean water eddies

Abstract: In this work, we obtain new results on the manifestation of meddies (or of other deep eddies)at the sea-surface, further developing the results by Bashmachnikov and Carton (2012). The quasigeostrophic equations are used to describe a near-axisymmetric vortex in the upper ocean, forced at its lower boundary by the isopycnal elevation of a moving meddy. The solution thus obtained provides a better approximation of the characteristics of meddy surface signals. The results show that in subtropics large meddies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
(101 reference statements)
2
9
0
Order By: Relevance
“…10d). For example, Ceres was observed to strongly weaken after crossing the 890 Azores Current (Richardson and Tychensky, 1997;Bashmachnikov et al, 2014). 891 892 The Rossby number, the ratio of meddy relative vorticity to the Coriolis parameter, 893…”
mentioning
confidence: 99%
“…10d). For example, Ceres was observed to strongly weaken after crossing the 890 Azores Current (Richardson and Tychensky, 1997;Bashmachnikov et al, 2014). 891 892 The Rossby number, the ratio of meddy relative vorticity to the Coriolis parameter, 893…”
mentioning
confidence: 99%
“…These new sensors will allow the measurement of sea surface height features at submesoscale, a scale already attained by ocean color (see Gaultier et al, 2013) or SST (sea surface temperature) sensors. Such high-resolution measurements of the sea surface, complemented by high-resolution in-situ measurements, such as VM-ADCP current profiling, seasoar or glider hydrological profiling, or seismic oceanographic transects, and the worldwide, intensive ARGO program of deep-ocean profilers, will provide a three-dimensional picture of surface and of subsurface mesoscale or submesoscale structures in the ocean (see also Filyushkin and Sokolovskiy, 2001;Bashmachnikov et al, 2012Bashmachnikov et al, , 2013Bashmachnikov et al, , 2014. Such highresolution and synoptic databases will allow a complete validation of simple process studies.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a larger depth of the Meddy core can diminish the eddy surface signal. Surface turbulent features, like surface eddies shed by fronts (e.g, the Azores front [Bashmachnikov et al (2013), Bashmachnikov et al (2014)]) can also perturb the anticyclonic signature of a Meddy and enhance the signal or make it disappear. Bashmachnikov and Carton (2012) found that stronger upper ocean stratications can also reduce the SSH bumps related to an underlying Meddy.…”
Section: Introductionmentioning
confidence: 99%